2020
DOI: 10.1002/ajp.23204
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography cannot be used to approximate core body temperature in wild primates

Abstract: Understanding the physiological processes that underpin primate performance is key if we are to assess how a primate might respond when navigating new and changing environments. Given the connection between a mammal's ability to thermoregulate and the changing demands of its thermal environment, increasing attention is being devoted to the study of thermoregulatory processes as a means to assess primate performance. Infrared thermography can be used to record the body surface temperatures of free-ranging anima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Physical activity causes heat to be dissipated by skeletal muscles, increasing outer body surface temperature [ 34 ], and even resting positions have to be considered, because animals resting on their side on cool or moist ground will have cooler areas in the thermogram [ 97 ]. Furthermore, in horses, Jansson and colleagues did not find a correlation between maximal eye temperature and rectal temperature [ 96 ], while McFarland and colleagues confirmed that surface temperature is more predictive of environmental temperature rather than core temperature, and it should not be used as an indicator of core temperature in wild primates [ 98 ]. In mice, the orexinergic system partially controls thermogenesis, influencing sympathetic responses that may reflect inter-individual differences [ 61 ], and it is worth recounting that orexins are peptides present in various vertebrates classes [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity causes heat to be dissipated by skeletal muscles, increasing outer body surface temperature [ 34 ], and even resting positions have to be considered, because animals resting on their side on cool or moist ground will have cooler areas in the thermogram [ 97 ]. Furthermore, in horses, Jansson and colleagues did not find a correlation between maximal eye temperature and rectal temperature [ 96 ], while McFarland and colleagues confirmed that surface temperature is more predictive of environmental temperature rather than core temperature, and it should not be used as an indicator of core temperature in wild primates [ 98 ]. In mice, the orexinergic system partially controls thermogenesis, influencing sympathetic responses that may reflect inter-individual differences [ 61 ], and it is worth recounting that orexins are peptides present in various vertebrates classes [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“… This can be achieved by connecting the temperature logger to a thermocouple that is either coated in black insulation tape (see Jerem et al, 2018; Jerem et al, 2019) or embedded in an aluminum or copper plate painted with a flat black paint (see Giloh et al, 2012; McFarland et al, 2020). See also the review by Tattersall (2016) for a discussion of calibration methods and practical considerations to ensure the quality of the temperature measurements obtained from thermal images. …”
mentioning
confidence: 99%
“…In contrast, McFarland et al [ 64 ] evaluated thermal responses in different body regions of vervet monkeys ( Chlorocebus pygerythrus ), including the dorsum and face, especially the nasal region. Results revealed that although the temperature of the nasal region presented significant changes, they were not related to body temperature and thus could not be considered an effective approach to measure vasoconstriction accurately.…”
Section: Facial Windowsmentioning
confidence: 99%
“…Scientific evidence has shown that IRT has clinical and diagnostic applications with zoo animals [ 64 ]. However, effectively implementing this tool requires considering factors that can influence recordings and their interpretation.…”
Section: Limitations On the Use Of Irt In Wildlife Species Under Huma...mentioning
confidence: 99%